Cost-benefit of being a congressman in Peru - Mauro Machuca, Raúl (2008)
Cost-benefit analysis is an economic tool used to evaluate both private and social projects. It is about comparing the costs of investing in a certain project against the current valuation of all future benefits. It is necessary to reform Parliament so that society sees the cost of its activities. In Peru, the congress behaves like a monopolist in the production of laws, which is why the participation of civil society is necessary.